Developing a thermal confort index for vegetated open space in cities of arid zones - Ruiz, María Angélica (2014)
The degree of thermal comfort that people experience in open spaces is one of the determinants for use, especially in areas with extreme climates. It has a wide range of indices in the international literature. However, the study of five indices (THI, PE, TS, PMV and COMFA) regarding subjective responses presented low percentages of predictive successes in the city of study, characterized by an arid climate and intense urban vegetation. Therefore, the aim of this work is to develop a new thermal comfort index to predict more accurately the thermal sensation of the local residents. For this, there were campaigns monitoring of microclimatic parameters and field surveys about the real sensation of the people on a pedestrian street of Mendoza Metropolitan Area (MMA) in both winter and summer. The proposed new model is established through the correlation of environmental variables and individual subjective responses. The multivariate correlation is performed by linear regression. The theory of Akaike´s information is used as criterion to model selection. The new model IZA is a lineal relation of air temperature, relative humidity, wind speed and solar radiation, generally all available weather variables. We found a high correlation between subjective responses and the new model. Besides the Pearson coefficient which gives the new index is higher than other traditional indices evaluated. The percentage of success of the new index exceeds 85%, demonstrating the effectiveness of the proposed model. In conclusion, the use of IZA as a predictor of thermal comfort will allow a fair assessment of the effect of design and composition of space on your comfort conditions, without the need to carry out thermal perception surveys. This will facilitate the evaluation and decision-making regarding the thermal rehabilitation of open spaces.